'Transcendent' genealogical and kinship relations: afterlife in African traditional religions - Naidu, Maheshvari (Journal of Dharma, 2012)
Ancestor worship, in most instances is positioned within a cosmological worldview that represents a very specific conceptualization of this world, living in this world and life after death for the individual. It speaks to a worldview where there are levels of involvement and genealogical linkage between the living and the dead, as well as the world of the living and the world of the dead. In this perception, a dying person does not go to another world but changes merely his or her physical mode of existence to that of a spiritual one. Mbiti points out that African Traditional Religion is an “ontological phenomenon” that pertains to the question of existence or being, and draws our gaze to the detail that this is a religious worldview where the individual is “immersed in continuous religious participation which starts before birth and continues after death.”
free
Keywords: African independent churches; Ancestors – Religious aspects; Christianity and African religions; Dead – Religious aspects – African religion; Future life – African religion; Ritual